Simvastatin Inhibits LPS-induced Alveolar Bone Loss during Metabolic Syndrome - Jin, J. (SAGE Publications, 2014)
Studies in recent years have shown a positive relationship between metabolic syndrome (MS) and periodontal disease (PD). Given that patients with MS take statins to reduce cholesterol, and statins also have anti-inflammatory effects, it is important to determine if statin intake hinders the progression of MS-associated PD. In this study, PD was induced in Zucker fat rats (ZFRs), an animal model for MS, and in control lean rats by periodontal injection of Aggregatibacter actinomycetemcomitans lipopolysaccharide (LPS), while simvastatin was given to some of the rats via gavage. After 4 wk of treatment, alveolar bone loss was determined by micro-computed tomography. To explore the underlying mechanisms, we determined the effect of simvastatin on tissue inflammation and the expression of molecules involved in osteoclastogenesis. Results showed that while bone loss was increased by LPS in both ZFRs and the control lean rats, it was significantly more in the former than the latter. Simvastatin effectively alleviated bone loss in both ZFRs and the control rats. Results also showed that LPS stimulated leukocyte tissue infiltration and expression of molecules for osteoclastogenesis, but simvastatin significantly modulated the stimulation. This study demonstrated that simvastatin inhibited LPS-induced alveolar bone loss and periodontal tissue inflammation in rats with MS.